2021
DOI: 10.1590/1809-4422asoc20200030r2vu2021l1ao
|View full text |Cite
|
Sign up to set email alerts
|

Socio-environmental vulnerability in the São Paulo Macro-metropolis’ three main metropolitan regions: a socio-environmental indicators analysis indicators analysis

Abstract: In this article, the concept of socio-environmental vulnerability is empirically operationalized, with the objective of analyzing situations of socio-environmental vulnerability on intra-urban scale, in a group of 62 municipalities in the three main metropolitan regions of the Macro-metropolis of São Paulo State. The methodology associates two concepts from the recent literature on vulnerability - one social and the other physical-environmental - through an index that integrates socio-demographic indicators fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…As several studies have shown (Greiving et al, 2011;Swart et al, 2012;Timmerman et al, 2017, Reis et al, 2020Alves, 2021), when assessing climate change, urban vulnerability has become a key topic and an area that needs to be enhanced so that the interactions of the human systems with the environment and its mutual influences can be fully explored. The aim of this study is to set out the way the evolving concept of urban vulnerability can be understood and to outline what measures are being adopted in big cities to mitigate hydro-meteorological risks.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…As several studies have shown (Greiving et al, 2011;Swart et al, 2012;Timmerman et al, 2017, Reis et al, 2020Alves, 2021), when assessing climate change, urban vulnerability has become a key topic and an area that needs to be enhanced so that the interactions of the human systems with the environment and its mutual influences can be fully explored. The aim of this study is to set out the way the evolving concept of urban vulnerability can be understood and to outline what measures are being adopted in big cities to mitigate hydro-meteorological risks.…”
Section: Objectivesmentioning
confidence: 99%
“…various interactions, accompanied by great spatial heterogeneity and a multiplicity of time scales(Secchi, 2000; Batty, 2009;Alves, 2021). vulnerability and the tools required for hydro-meteorological risk disaster managementSpecial Edition -Mudanças climáticas e planejamento urbano: cenários e desafios…”
mentioning
confidence: 99%
“…In addition, the authors of [21] used global climate models to show that, as a consequence of climate change, streamflow in the São Francisco and Parnaíba rivers is projected to decline by 46% and 26%, respectively, in the upcoming decades. Previous studies have shown that socio-environmental vulnerability may increase significantly with a high frequency of climate extremes, especially in regions where the local population lives in a situation of poverty [22].…”
Section: Introductionmentioning
confidence: 99%